2010
DOI: 10.1007/s13353-010-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Dysmyelinating and demyelinating Charcot–Marie–Tooth disease associated with two myelin protein zero gene mutations

Abstract: Mutations in the myelin protein zero (MPZ) gene are the third most frequent cause of hereditary motor and sensory neuropathies (HMSN), also called Charcot-Marie-Tooth disorders (CMT). Only in case of recurrent mutations occurring in the MPZ gene is it possible to draw phenotype-genotype correlations essential for establishing the prognosis and outcomes of CMT1. We have surveyed a cohort of 67 Polish patients from CMT families with demyelinating neuropathy for mutations in the MPZ gene. In this study, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…It was found that a similar amino acid substitution at codon 132 (p. Pro132Leu) resulted in the focally folded myelin with degenerative changes. 31 Mutations in positions close to those described in this current case report were found in ClinVar and patients carrying these pathogenic variants had similar symptoms to those identified in the proband with the novel p.Pro133Leu substitution. A previous study described the p.Asn131Lys mutation in exon 3 of the MPZ gene, which is responsible for its adhesive properties.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It was found that a similar amino acid substitution at codon 132 (p. Pro132Leu) resulted in the focally folded myelin with degenerative changes. 31 Mutations in positions close to those described in this current case report were found in ClinVar and patients carrying these pathogenic variants had similar symptoms to those identified in the proband with the novel p.Pro133Leu substitution. A previous study described the p.Asn131Lys mutation in exon 3 of the MPZ gene, which is responsible for its adhesive properties.…”
Section: Discussionsupporting
confidence: 74%
“…It was found that a similar amino acid substitution at codon 132 (p.Pro132Leu) resulted in the focally folded myelin with degenerative changes. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The cumulative effect of two mild variants was hypothesized in a CMT family with simultaneous MFN2 and GDAP1 variants 24 . To the best of our knowledge, there have been a few compound heterozygous variants of MPZ 25‐27 . Regarding the compound heterozygous variant in our study, this patient was classified as demyelinating CMT.…”
Section: Discussionmentioning
confidence: 76%
“…Two mutations in the MPZ Gene (His81Tyr and Val113Phe) were report in a 45-year-old female with a peripheral neuropathy with demyelinating and axonal features, pes cavus and pupillary light-near dissociation with a less severe phenotype in comparison to a patient with single His81 Arg mutation [ 31 ]. In a study carried in the Polish population, Drac et al [ 32 ] described two CMT families in which the Ile135Thr and Pro132Leu mutations for the gene MPZ were identified. In the family carrying the Pro132Leu mutations, the sural nerve biopsy displayed hypomyelination-dysmyelination process.…”
Section: Discussionmentioning
confidence: 99%